2014
DOI: 10.1088/0953-8984/26/27/274204
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and composition dependence of short-range order and entropy, and statistics of bond length: the semiconductor alloy (GaN)1−x(ZnO)x

Abstract: Temperature and composition dependence of short-range order and entropy, and statistics of bond length: the semiconductor alloy (GaN) 1−x (ZnO) Abstract. We present total energy and force calculations on the (GaN) 1−x (ZnO) x alloy. Site-occupancy configurations are generated by Monte Carlo (MC) simulations, based on a cluster expansion (CE) model proposed in a previous study. Surprisingly large local atomic coordinate relaxations are found by density-functional calculations using a 432-atom periodic supercell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…In Figure , the change in the formation energy per atom is plotted against the number of Ga–N bonds in the cell. Indeed, there is a decrease in ΔnormalHf with increasing number of Ga–N bonds, indicating that more Ga–N bonds yield more stable configurations, which also has been found in other studies . This result makes the formation of nano‐sized GaN clusters to be a probable consequence of the post‐deposition anneals, so that more Ga–N bonds are formed to lower the energy of the system, assuming that Ga and N are sufficiently mobile during the post‐deposition annealing to find a more energetically favorable position.…”
Section: Resultssupporting
confidence: 80%
“…In Figure , the change in the formation energy per atom is plotted against the number of Ga–N bonds in the cell. Indeed, there is a decrease in ΔnormalHf with increasing number of Ga–N bonds, indicating that more Ga–N bonds yield more stable configurations, which also has been found in other studies . This result makes the formation of nano‐sized GaN clusters to be a probable consequence of the post‐deposition anneals, so that more Ga–N bonds are formed to lower the energy of the system, assuming that Ga and N are sufficiently mobile during the post‐deposition annealing to find a more energetically favorable position.…”
Section: Resultssupporting
confidence: 80%
“…In constructing the cluster expansion model, the total energy of a specific configuration is calculated in its relaxed structure. Local relaxations of surprisingly large magnitude are found in our subsequent study 26 . The aim of the present study is to construct DFT-affordable supercells whose structural correlations accurately reflect the SRO found by the above approach.…”
Section: Introductionsupporting
confidence: 59%
“…12. While the x-dependence of the configurational mixing entropy is symmetric 26 , the x-dependence of the phonon mixing entropy is highly asymmetric, indicating that the inclusion of the vibrational free energy into the alloy thermodynamics could alter the shape of the phase diagram.…”
Section: B Atomic Electronic and Vibrational Propertiesmentioning
confidence: 99%
“…We conclude that (KDP) X (ADP) 1−X mixed crystal system is similar to the alloy systems like (GaN) 1−x (ZnO) x [20], where it was found that the compositional fluctuations lead to strong dependence of bond length on the local chemical environment. Understanding the role of order and disorder in determining physical properties such as bond length is complicated by the difficulty in modelling the numerous local chemical environments within the crystal systems.…”
Section: Structural Comparisonsupporting
confidence: 56%